To Study the Efficacy of Racecadotril for Treatment of Acute Watery Diarrhea in Children (Medical Forum Monthly, 2020)
Objective: To study the efficacy of racecadotril on decreasing no of stools in pediatric population presenting with acute watery diarrhea to decrease the length of hospital stay.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Pediatric Unit MTI, Mardan Medical Complex from April to August 2019.Materials and Methods: 120 children, aged 6 months to 2 years, were included and placed on random basis in a racecadotril or placebo group. Criteria of inclusion was patients diagnosed with acute gastroenteritis. Patient having any other disease or allergy were excluded. Racecadotril and placebo were given at a dose of 10 mg p/o TDS for children below 1 year, 30mg P/O TDS for children above 1 year. Data were collected and analyzed in SPSS 20.Results: Mean age was 9.8 months. Females were 45.8% whereas males were 54.2%. Stool frequency at 48 hours in Racecadotril group were significantly decreased with a (mean of 5.10/SD 2.589/ P-value 0.012 as compared to Placebo (mean of 7.22 /SD 2.835). Mean age was 9.8 months. females were 45.8% whereas males were 54.2%. Stool frequency at 48 hours in Racecadotril group were significantly decreased with a (mean of 5.10/SD 2.589/ P-value 0.012 as compared to Placebo (mean of 7.22 /SD 2.835). Length of hospital stay was lower in racedo category 76.40 hours /SD 31.08610/P – value: 0.029 as compared to placebo with a mean of.92.400 hours /SD 38.9816. Length of hospital stay was lower in racedo category 76.40 hours /SD 31.08610/P – value: 0.029 as compared to placebo with a mean of.92.400 hours /SD 38.9816.Conclusion: We have concluded from this study that racecadotril can be effectively used for treating acute gastroenteritis in pediatric population. It decreases stool frequency that will reduce duration of hospital stay.